Advancing acute MI care in densely populated low- and middle-income countries (LMICs): innovative stand-alone chest pain units for expedited triage and timely managementResearch in context - Nadeem Qamar; Jawaid A. Sial; Tahir Sagir; Zair Hussain; Ali Zain Shah; Kamran Khan; Jehangir Ali Shah; Musa Karim; Shueeta Kumari; Sohail Khan; Sabha Bhatti; Abdul Hakeem (Elsevier, 2024)
Summary: Background: The incidence of myocardial infarction (MI) and its adverse effects on health and mortality remain high in densely populated low- and middle-income countries (LMICs). To address the issue of densely populated areas and timely access to primary PCI, chest pain units (CPUs) were deployed at strategic locations in Karachi, with a populace of over 23 million people. This study describes the results of this initiative in expediting MI care. Methods: Between 2017 and 2023, 18 CPUs, each with a cardiologist, technician, ECG machine, crash cart and an ambulance were placed in high density areas. Findings: A total of 915,564 patients were seen at 18 CPUs over the study period. 692,444 (75.6%) were categorized as non-cardiac and subsequently discharged. 223,120 (24.6%) patients were directed for additional care. Of these, 9% had ST elevation myocardial infarction (STEMI) (19, 580), 29% NSTE ACS/Unstable angina, and 31% with various other cardiac conditions. Additionally, 31% were referred for medical outpatient evaluation. CPU inception led to a significant annual growth (16-20%) in primary PCI procedures at NICVD, totaling 20,000 by 2022-2023. The median first medical contact to device time was 100 min (IQR 80-135), while total ischemic was 232 min (IQR: 172-315; 5th −95th %le: 50-920). The overall in-hospital mortality rate for patients undergoing primary PCI was 5.58%, with a range between 5.1% and 6.9% through the study period. Interpretation: Novel standalone chest pain units, operational from 2017 in Karachi, Pakistan, have expedited triage and enhanced the timely management of AMI. This initiative's transformative impact presents a model that resonates beyond borders, serving as a role model for global healthcare systems. Funding: The CPU and primary PCI program is fully funded by the government of Sindh. No specific funding was allocated for this study.